Money Market and Capital Market in Islamic Economic Perspective - Angkat, Ervina Yulia; Riduan, Muhammad (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The research theme is the financial and banking institutions. This article aims to look at the money market and the capital market in the perspective of Islam. The article is the result of the study of literature. Differences in the Islamic capital market with conventional capital market can be seen in the instruments and mechanisms of the transaction. Islamic stock index difference with conventional stock indexes lies in the issuer’s shares of criteria that must comply with the principles of sharia. The main instruments are traded in the Islamic capital markets and capital markets are conventional stocks. Expected to Islamic capital market is really a meeting place between people who are in need of capital to investors who want to invest in productive sectors.